2019
DOI: 10.1021/acssuschemeng.8b05873
|View full text |Cite
|
Sign up to set email alerts
|

Clean Synthesis of 5-Hydroxymethylfurfural and Levulinic Acid by Aqueous Phase Conversion of Levoglucosenone over Solid Acid Catalysts

Abstract: Levoglucosenone (LGO) is an emerging biorenewable platform for the fine and commodity chemical industries. Herein, we report an aqueous phase conversion of LGO to 5-hydroxylmethylfurfural (HMF) and levulinic acid (LA) over solid acid catalyst. Several types of solid acid catalysts such as zeolites, strongly acidic ion-exchange resin, and sulfonated activated carbon were investigated for this reaction. Among the tested catalysts, ZSM-5 and Amberlyst 70 showed the best performances for selectively producing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Of the 94 productso btained from these sugars, 25 were selected as involving feasible technologiest hat are suitablef or large-scale prototype testing in ap ilot plant. [11][12][13] Other research has focused on optimizingh eterogeneous catalysts for dehydration reactions involving both metal catalysts [14][15][16][17][18][19][20] and supported ionic liquids. [3] The main route to form HMF is by the dehydration of sugars, [4] and important resultsh ave been achieved for HMF production using ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 94 productso btained from these sugars, 25 were selected as involving feasible technologiest hat are suitablef or large-scale prototype testing in ap ilot plant. [11][12][13] Other research has focused on optimizingh eterogeneous catalysts for dehydration reactions involving both metal catalysts [14][15][16][17][18][19][20] and supported ionic liquids. [3] The main route to form HMF is by the dehydration of sugars, [4] and important resultsh ave been achieved for HMF production using ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Deep eutectic solvents andw ater have also been investigated for the dehydration of fructose into HMF but improvedy ields are still needed. [11][12][13] Other research has focused on optimizingh eterogeneous catalysts for dehydration reactions involving both metal catalysts [14][15][16][17][18][19][20] and supported ionic liquids. [21,22] In particular, ionic liquidsw ith halide counteranions have provenv ery efficient for the production of HMF from fructose, glucose,a nd cellulose with both Brønsted and Lewis acid catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, a number of acid catalysts have been developed to efficiently catalyze the various acid‐catalyzed reactions . Homogeneous acid catalysts (HCl, H 2 SO 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Over the past decade, a number of acid catalysts have been developed to efficiently catalyze the various acid-catalyzed reactions. [22][23][24][25][26][27][28][29] Homogeneous acid catalysts (HCl, H 2 SO 4 , etc.) exhibit good catalytic performance due to their homogeneous distribution in protic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The target product from LGO in current market is limited mainly to dihydrolevoglucosenone, which is used as solvent (Sherwood et al, 2014), but extensive studies have revealed the potential to be a type of platform chemical similarly to HMF (Krishna et al, 2018). Recent studies (Krishna et al, 2016;He et al, 2017;Huang et al, 2019b) have identified LGO as an alternative feedstock for HMF.…”
Section: Introductionmentioning
confidence: 99%